Triathlon and the multisport athlete - Cipriani, D. J.; Swartz, J. D.; Hodgson, C. M. (Journal of Orthopaedic & Sports Physical Therapy, 1998)
The sport of triathlon is a rapidly growing arena for athletic competition and training. Men and women of various fitness backgrounds have become involved in this sport that involves the disciplines of swimming, cycling, and running. Training for multiple sports has the advantages of providing the athlete with a variety of means of maintaining fitness in the event of an injury. On the other hand, multisport training may also contribute to a special category of injuries, those related to the cumulative effects of cross-training. The purpose of this paper is to provide a review of the literature regarding triathlon training and injuries. A survey of a local triathlon club regarding the incidence of injuries is presented, and comparisons are made with previously published surveys. Finally, this paper attempts to outline the training conditions of the triathlete and to provide readers with strategies for injury management.